A comparative multi‐reference configuration interaction study of the low‐lying states of two thione isomers of thiophenol. Issue 16 (11th June 2020) - Lima, Filipe Belarmino de; Pereira Rodrigues, Gessenildo; de Lucena Júnior, Juracy Regis; Ventura, Elizete; Fausto, Rui; Reva, Igor; do Monte, Silmar Andrade
Abstract: Multi‐reference configuration interaction, MR‐CI (including extensivity corrections, named +Q), calculations were performed on the S0 –S3 states of cyclohexa‐2, 4‐diene‐1‐thione (thione 24 ) and cyclohexa‐2, 5‐diene‐1‐thione (thione 25 ), which are thione isomers of thiophenol. Several types of uncontracted MR‐CIS and MR‐CISD wavefunctions were employed, comprising MR‐CI expansions as large as ~365 × 10 6 configuration state functions. The nature of the studied excited states was characterized. Vertical excitation energies (Δ E ) and oscillator strengths ( f ) were computed. The most intense transitions (S0  → S2 for 24 and S0  → S3 for 25 ) did not change with the wavefunction, although a variation as large as ~1 eV was obtained for the S3 state of 24, at the highest (MR‐CI+Q) level. On the other hand, Δ E changed at most by ~0.56 eV for 25 as the wavefunction changes, at the same level. The S1 state of both thiones was found to have n π * character and is in the visible region. For 24, S2 and S3 are ππ * and n π * states, respectively, while for 25 the reverse order is obtained. S2 and S3 are in the range ~3.5 to 5.2 eV, again at the highest level. It is the first time that the excited states of the title molecules are studied. The computed results agree with the experimental onset of photoreactions of thiones 24 and 25 found by Reva et al ( Phys. Chem. Chem. Phys., 2015, 17, 4888). Abstract : A correct description of the properties of the excited states is the first step towards a deep understanding of the photochemistry of compounds. This article shows accurate results for some excited states of two new thione isomers of thiophenol, which can help to discriminate between these species as well to follow spectroscopically their interconversions.